On bullying and prejudice from the Symbolic and the Imaginary - de Sousa e Castro Noya Pinto, Fernanda (2021)
In this article, oriented by the question about what is the place of the similar function, we try to approach the participation of the subjective dimension present in two forms of violence: bullying and prejudice. We present readings of speeches by authors and victims of bullying and authors of prejudiced actions, based on the psychoanalytic ideas of the Symbolic and the Imaginary, as a contribution to the understanding of the unconscious dimension that sustains the relationship with the different. We believe that each of the two violent ways of dealing with difference - bullying and prejudice - have their own and quite distinct aspects. It was possible to verify that the Symbolic and Imaginary registries, described by psychoanalysis, can help in the understanding of such phenomena, once they offer references to think about the ways of seeing the other, the differences, and what causes some discomfort. More specifically, the Imaginary serves as a basis for thinking about bullying, while the Symbolic can help us understand prejudiced actions. Our contribution was to bring elements, especially those that are subconscious, which allow us to rethink aspects involved in the forms of violence investigated, from an interpretation based on Lacanian psychoanalysis.